2010
DOI: 10.1259/bjr/64623458
|View full text |Cite
|
Sign up to set email alerts
|

Risk of deterministic effects during endovascular aortic stent graft implantation

Abstract: ABSTRACT. Since the 1990s, stent graft implantation for aortic pathology has become an alternative to extensive surgical procedures in some patients. Indeed, many patients with such pathology are now treated endovascularly. Only limited data concerning the risk of a deterministic effect during aortic stent graft implantation are available. Accordingly, 179 consecutive patients treated in our institute between October 2002 and July 2008 with endovascular aortic stent grafts were included in this study. Dosimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Similar correlations were observed by Blaszak, et al (2009, and Kuhelj, et al (2010), but not by Pannucio (2011). found that the radiation burden is also influenced by the operative strategy chosen by the surgeon, that depends on the clinical presentation.…”
Section: Patient Related Factorssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar correlations were observed by Blaszak, et al (2009, and Kuhelj, et al (2010), but not by Pannucio (2011). found that the radiation burden is also influenced by the operative strategy chosen by the surgeon, that depends on the clinical presentation.…”
Section: Patient Related Factorssupporting
confidence: 76%
“…However, if concern is raised over skin dose, the radiochromic film can be removed from the bed during repair and examined by bare eye in normal light at the operation room for a rough dose assessment. Kuhelj, et al (2010) analyzing the dosimetric data on 179 patients treated using a suboptimal mobile C-arm unit found a 0.44 Gy median PSD (range 0.12 to 2.7 Gy). Investigators at Cabridge reported a 0.85 Gy median PSD on 96 repairs (Weerakkody, et al 2008;.…”
Section: Assessment Of Deterministic Effects To Patientmentioning
confidence: 99%
“…Our estimated total mean peak skin dose was 0.489 Gy, while maximum and minimum values were: 1.78 Gy and 0.014 Gy. PSD allows us to determine the possibility for a patient to receive a radiation skin injury (10,23). Suggested threshold is 2 Gy (11,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 patients had PSD higher than 1.5 Gy and none of the skin injuries, like erythema were reported. Other studies showed that their estimated total mean PSD was 0.44 Gy, 1.01 Gy (21,23). Still, estimating PSD from KAP is problematic because during interventional procedures the X-ray tube is moved around the patient, thus irradiating different areas of skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation